THE ECONOMIC EVALUATION TO CIPARAGE COASTAL FISHING PORT SERVICES, KARAWANG REGENCY: CONSUMERS SIDES APPROACH - Nurfadilah, Annisa; Dewi, Dian Ayunita Nugraheni Nurmala; Wibowo, Bambang Argo (Universitas Tidar, 2022)
Karawang Regency has a fishing port with the status of a Coastal Fishing Port. Fishing Ports provide services to fishermen as users of the facilities available at the port. One kind of service is administrative service at the Fishing Port, this service is related to fishing operational activities. The purposes of this study were to analyze the fishermen's satisfaction level with fishing port services and to find out what services are considered important by fishermen. This study analyzed the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods to measure fishermen's satisfaction. Based on the results of the study indicate that the assessment of satisfaction with services at the Ciparage Coastal Fishing Port is classified in the satisfied category. This is shown by the value of the Fisher Satisfaction Index, which is 76.565%. The service that has the highest value is the attributes of the facilities at the Fish Auction Place (TPI) and the attitude of the administration officers at the port. The conclusion of this condition should be maintained by the port, the suggestion from this research is that there is a need for an expansion of the pier facilities at the port so that it can accommodate a number of vessels to lean.